Dorothea Graumann, Beethoven's Dorothea-Cäcilla - Unknown:::Creator::::::::::::; Oechs, J. D.:::Contributor:::::::::::: (Stuttgart; Germany; Edward Hallberger)
Portrait of Dorothea Graumann (born von Ertmann) playing the piano by unidentified artist.; Possibly based on ivory miniature by J.D. Oechs.